Ethnography and Religious Anthropology of Cuba: Historical and Bibliographical Landmarks - Emma Gobin; Géraldine Morel (Ateliers d'Anthropologie)
The development that Cuban studies are undergoing today, particularly the ethnographic study of religious practices usually characterised as “of African origin”, is no coincidence. This introductory paper offers an overview of the socio-historical conditions that have favoured this renaissance, placing them in the Cuban ideological and political context. In order to establish a few reference points in a field of research that has become particularly dynamic, it also outlines some important trends in the scholarship on Cuban religions and briefly lists and comments on recent studies. Whether produced in Europe, the United-States or Cuba itself, these works often attest to distinct orientations which this introduction broadly touches upon before delving into the main features of the ‘Afro-Cuban’ religious field and the research themes emerging from this collection, which also reflect some important approaches of contemporary anthropology of religion.